OR18-3 Gonadal Function in Human Immunodeficiency Virus (HIV)-Infected Men Assessed by Isotopic Dilution-Liquid Chromatography-Tandem Mass Spectrometry (ID-LC-MS/MS) and Chemiluminescent Immunoassay - De Vincentis, Sara (J Endocr Soc, 2019)
BACKGROUND: HIV-infection is associated to premature decline of serum T(1,2). However, prevalence and biochemical characterization of hypogonadism in HIV-infected men are still to be well defined(1,2). AIM: To evaluate the gonadal status in HIV-infected men by assessing circulating total T (TT) with either ID-LC-MS/MS or chemiluminescent immunoassay. METHODS: Prospective, cross-sectional, observational study on HIV-infected men with ongoing Highly Active Antiretroviral Therapy (HAART). Serum TT, gonadotropins and sex hormone-binding globulin (SHBG) were measured by chemiluminescent immunoassay. TT was also assessed by the gold standard ID-LC-MS/MS. Free T (FT) was calculated by Vermeulen equation. Hypogonadism was defined as serum TT levels below 320 ng/dL and/or free T levels below 64 pg/ml. Statistical analysis: Categorical variables were compared using Chi-Square test, while correlations were performed using linear regression models. RESULTS: 315 consecutive HIV-infected men were enrolled (mean age 45.56±5.61 years; average duration of HIV-infection 16.57±10.45 years). Considering serum TT levels assessed by LC-MS/MS and immunoassay, 11 patients out of 233 (4.8%) and 10 patients out of 315 (3.2%) had T deficiency, respectively. TT combined with luteinizing hormone (LH) levels was used to classify hypogonadism. No difference was found comparing the two methodologies used for TT measurement (p=0.914). 56 patients (17.8%) showed SHBG above the normal range (>71.4 nmol/L). Considering calculated FT, the incidence of hypogonadism raised to 6.9% using either immunoassay or LC-MS/MS, with no difference between methodologies (p=0.895). Including compensated form of hypogonadism, the prevalence raised to 13% for TT and to 15% for FT. FT showed an inverse relation with age (-0.340,p<0.0001,R(2)=0.116), years of infection (-0.339,p<0.0001,R(2)=0.120) and years of HAART (-0.346,p<0.0001,R(2)=0.117), but not with BMI of patients. CONCLUSIONS: To the best of our knowledge, this is the first properly-designed prospective study aiming to investigate the gonadal status of HIV-infected men with both LC-MS/MS and chemiluminescent assay, together with gonadotropins. In HIV-infected patients a) the two methodologies have equivalent reliability in TT measurement; b) SHBG for calculated FT is essential for the detection of T deficiency, revealing the real prevalence of hypogonadism in this context; c) duration of HIV-infection and HAART seem to be potent predictive factors for serum FT levels, suggesting a concomitant negative effect of virus per se and antiretroviral drugs on gonadal function. REFERENCES(1)Rochira V et al. Premature decline of serum total testosterone in HIV-infected men in the HAART-era. PLoS One. 2011;6(12):e28512. (2)Rochira V & Guaraldi G. Hypogonadism in the HIV-infected man. Endocrinol Metab Clin North Am. 2014 Sep;43(3):709-30.